Self-template construction of nanoporous carbon nanorods from a metal–organic framework for supercapacitor electrodes. Issue 37 (6th June 2018) - Yang, Ya-Wen; Liu, Xuan-He; Gao, En-Peng; Feng, Tian-Tian; Jiang, Wen-Jie; Wu, Jing; Jiang, Hao; Sun, Bing
Abstract : The Ni-CAT-derived porous carbon materials at 800 °C remain regular with a rod-like morphology and exhibit enhanced capacitive performance. Abstract : The morphologies and structures of nanostructured carbons generally influence their catalysis, electrochemical performance and adsorption properties. Metal–organic framework (MOF) nanocrystals usually have various morphologies, and can be considered as a template to construct nanostructured carbons with shaped nanocubes, nanorods, and hollow particles by thermal transformation. However, thermal carbonization of MOFs usually leads to collapse of MOF structures. Here, we report shape-preserved carbons (termed as CNRods) by thermal transformation of nickel catecholate framework (Ni-CAT) nanorods. Supercapacitors of CNRods treated at 800 °C were demonstrated to have enhanced performance due to their structural features that facilitate electron conduction and ion transport as well as abundant O content benefiting the wettability of the carbon materials. This may provide a potential way to explore novel carbon materials for supercapacitors with controllable morphologies and high capacitive performance.